Răspuns :
[tex]a= \sqrt{30}-12 \sqrt{6}- \sqrt{4}+2 \sqrt{3}+3 \sqrt{5}-2 \sqrt{6} +5[/tex]
[tex]a= \sqrt{30}-12 \sqrt{6}+2 \sqrt{3}+3 \sqrt{5}-2 \sqrt{6} +3[/tex]
[tex]a= \sqrt{30}-14\sqrt{6}+2 \sqrt{3}+3 \sqrt{5} +3[/tex]
[tex]b=2\sqrt{8}- \sqrt{14}+4 \sqrt{6}- \sqrt{22} +4+ \sqrt{10}[/tex]
[tex]b=2*(2 \sqrt{2} )- \sqrt{14}+4 \sqrt{6}- \sqrt{22} +4+ \sqrt{10}[/tex]
[tex]b=4 \sqrt{2} - \sqrt{14}+4 \sqrt{6}- \sqrt{22} +4+ \sqrt{10} [/tex]
[tex]m_g= \sqrt{a*b} [/tex]
[tex]m_g= \sqrt{(\sqrt{30}-14\sqrt{6}+2 \sqrt{3}+3 \sqrt{5} +3)*(4 \sqrt{2} - \sqrt{14}+4 \sqrt{6}- \sqrt{22} +4+ \sqrt{10})}[/tex]
De aici cred ca te descurci ;)
[tex]a= \sqrt{30}-12 \sqrt{6}+2 \sqrt{3}+3 \sqrt{5}-2 \sqrt{6} +3[/tex]
[tex]a= \sqrt{30}-14\sqrt{6}+2 \sqrt{3}+3 \sqrt{5} +3[/tex]
[tex]b=2\sqrt{8}- \sqrt{14}+4 \sqrt{6}- \sqrt{22} +4+ \sqrt{10}[/tex]
[tex]b=2*(2 \sqrt{2} )- \sqrt{14}+4 \sqrt{6}- \sqrt{22} +4+ \sqrt{10}[/tex]
[tex]b=4 \sqrt{2} - \sqrt{14}+4 \sqrt{6}- \sqrt{22} +4+ \sqrt{10} [/tex]
[tex]m_g= \sqrt{a*b} [/tex]
[tex]m_g= \sqrt{(\sqrt{30}-14\sqrt{6}+2 \sqrt{3}+3 \sqrt{5} +3)*(4 \sqrt{2} - \sqrt{14}+4 \sqrt{6}- \sqrt{22} +4+ \sqrt{10})}[/tex]
De aici cred ca te descurci ;)